2014
DOI: 10.1111/ced.12499
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of injection with poly-L-lactic acid compared with hyaluronic acid for correction of nasolabial fold: a randomized, evaluator-blinded, comparative study

Abstract: PLA provides noninferior efficacy compared with HA 6 months after being used to treat moderate to severe nasolabial folds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The sample size was calculated with a power of 80%. 11 The differences between pre-and posttreatment were analyzed by a paired t-test, and the comparisons between the groups were performed using independent 2-sample t-tests with a false discovery rate method. To determine age effect, independent t-tests with the false discovery rate method and chi-square tests were used.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated with a power of 80%. 11 The differences between pre-and posttreatment were analyzed by a paired t-test, and the comparisons between the groups were performed using independent 2-sample t-tests with a false discovery rate method. To determine age effect, independent t-tests with the false discovery rate method and chi-square tests were used.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the efficacy and safety of PDLLA microspheres injections for the correction of nasolabial folds were compared with those of HA. PDLLA microspheres were not inferior to HA [22] , and 30 subjects completed the 24-month long-term safety evaluation follow up, which showed that PDLLA microspheres are safe and effective for use as fillers for nasolabial fold correction [23] . Complications such as granuloma formation [24][25][26][27] and accidental vascular occlusion [26][27][28] could occur, similar to other subdermal fillers, and need to be investigated further.…”
Section: Discussionmentioning
confidence: 90%
“…Of particular importance to us is the fact that the use of a needle is not capable of depositing RHA homogeneously in the skin of the face, and more specifically because we humans loose collagen all over the surface of our skin but still injectors treat specific areas such as the nasolabial folds, the lips, or the frontal aspect of the cheeks. [ 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…We advocate that depositing RHA in small amounts through large surfaces of the skin is also better to induce fibroblasts to synthesize new collagen. It is very clear that RHA can enhance the manufacture of new collagen and it does not seem worse than other products;[ 24 27 28 ] One recent study detected that RHA could improve 1.54 points in the Wrinkle Severity Rating Scale in comparison with 2.09 points improved by PLLA. Second, we believe that all HA are composed of particles some of which are “glued” with noncross-linked HA.…”
Section: Discussionmentioning
confidence: 99%